Representing national images of self and others through China’s diplomatic discourse: A corpus-based study - Feng Pan; Weixiao Li; Tao Li (PLoS ONE, 2026)
Drawing on van Dijk’s Ideological Square framework, this paper adopts a corpus-based method to examine the discursive strategies in their responses by the spokespersons for China’s Ministry of Foreign Affairs during regular press conferences amid a public health crisis. The analysis focuses on how these discursive strategies shape the national images of China and the other four permanent members of the United Nations Security Council. The results show that (1) the spokespersons actively employed communicative discursive strategy to clarify China’s stance and international cooperation initiatives while also using offensive discourse strategy to counter criticisms from US-led Western nations and media regarding the virus and the pandemic; (2) although the spokespersons’ discourse generally aligns with van Dijk’s Ideological Square of positive self-presentation and negative other-presentation, this model is not fixed but subject to dynamic changes driven by the self-serving principle. It is argued that factors such as diplomatic ideology, geopolitical relations, and traditional Chinese culture underlie the spokespersons’ use of discursive strategies and national images representations. This study contributes to reconceptualizing an existing discourse model by offering data-driven insights into the operational mechanisms of ideological discourse in the contexts of global political communication and national image construction.